Study of Kazakhstan`s coals burning efficiency of long-term combustion boilers up 100 kW - A.V. Atyaksheva; B.A. Zhakishev; Zh.K. Taybasarov; Zh.Zh. Taybasarova; M. Karagaeva (Қарағанды университетінің хабаршысы. Физика сериясы)
Today more than 30 % of boiler equipment in Kazakhstan has an increased moral and physical deterioration. The replacement of this equipment is made mainly by high-quality equipment of foreign manufacturers. However, boilers of foreign manufacturers are designed, as a rule, for operation on coals or other types of solid fuel with improved characteristics or fuel, which requires additional preparation. This ultimately reduces the operational and economic characteristics of the boiler and increases the cost of thermal energy for the consumer. Kazakhstan has a sufficient amount of solid fuel, which is possible for use in small-capacity boilers. However, most of this fuel is of poor quality. It seems to use low-quality coals in long burning boilers promising. When operating such boilers, additional heat is generated through the generation of synthesis gases generated in such boilers. To date, the production of long burning boilers is developing widely among domestic producers. Boilers of prolonged burning are becoming more and more popular. Analysis of the use of long burning boilers showed that when burning low-grade coals, their efficiency reaches 96-98 %. Lowpower heating boilers of traditional designs with the use of coals of improved characteristics have an efficiency of not more than 90 %. However, to date, there are no regulatory documents that regulate the performance characteristics of long burning boilers. Therefore, finding the optimal characteristics of the efficiency of fuel combustion, taking into account the standardized indicators, the question is very important, which determines the reliability, environmental friendliness and economical operation of the boiler. The analysis of the application of Kazakhstani fuels on long burning boilers with a capacity of up to 100 kW has been conducted and possible ways of improving the efficiency of these boilers have been determined.